Diagnosis and treatment of early gastric cancer: experience of one center - Zbigniew K. Kula; Wojciech Zegarski; Wojciech Jóźwicki (Gastroenterology Review)
Introduction : Gastric cancer is one of the most common malignant neoplasms in the world. Currently it constitutes the third cause of death among all malignancies. New endoscopic techniques have a potential to improve treatment results due to more frequent detection of early gastric cancer. Aim : To summarize our experience in diagnosis and treatment of early gastric cancer patients. Material and methods : We analyzed the results of endoscopic examination, histopathological findings and treatment methods in 16 patients who were diagnosed with early gastric cancer in the Endoscopy Unit of the Oncology Center in Bydgoszcz between 2014 and 2016. Results : Between 2014 and 2016 sixteen patients, 12 (75.0%) male and 4 (25.0%) female, were diagnosed with early gastric cancer. The average age of patients was 65.5 years. Surgery qualification concerned mainly G2 and G3 adenocarcinomas. In 12 (75.0%) patients total gastrectomy was performed, and 1 patient underwent wedge resection of the prepyloric part of the stomach. In 3 cases endoscopic submucosal dissection (ESD) was performed. Histopathological examination of both biopsy and postoperative material indicated 8 (50.0%) cases of intestinal-type adenocarcinoma, 7 (43.75%) cases of diffuse-type adenocarcinoma and 1 (6.25%) case of mixed-type adenocarcinoma. During the follow-up after treatment, none of the patients was diagnosed with local or distant recurrence. Conclusions : Accurate examination technique allows for detection of early gastric cancer. Selected cases of early gastric cancer may be treated with advanced endoscopic techniques.